Physio-Biochemical and Agronomic Responses of Faba Beans to Exogenously Applied Nano-Silicon Under Drought Stress Conditions - Desoky, El-Sayed M.; Mansour, Elsayed; El-Sobky, El-Sayed E. A.; Abdul-Hamid, Mohamed I.; Taha, Taha F.; Elakkad, Hend A.; Arnaout, Safaa M. A. I.; Eid, Rania S. M.; El-Tarabily, Khaled A.; Yasin, Mohamed A. T. (Frontiers in Plant Science, 2021)
Nano-silicon application is an efficient novel approach to mitigate the deleterious impacts of drought stress on field crops, which is expected to increase owing to climate change, especially in arid regions. Two-season field studies investigated the influence of foliar-applied nano-silicon (0.5, 1, and 1.5 mM) on physiological and biochemical attributes and their impacts on crop water productivity (CWP) and the agronomic traits of faba beans (Vicia faba). The plants were evaluated under two irrigation regimes: well-watered (100% ETc giving 406 mm ha−1) and drought stress (65% ETc giving 264 mm ha−1). It was found that drought stress significantly decreased gas exchange (leaf net photosynthetic rate, stomatal conductance, and rate of transpiration), water relations (relative water content and membrane stability index), nutrient uptake (N, P, K+, and Ca+2), flavonoids, and phenolic content. In contrast, drought stress significantly increased oxidative stress (H2O2 and O2·-) and enzymatic and non-enzymatic antioxidant activities compared with the well-watered treatment. These influences of drought stress were negatively reflected in seed yield-related traits and CWP. However, foliar treatment with nano-silicon, particularly with 1.5 mM, limited the devastating impact of drought stress and markedly enhanced all the aforementioned parameters. Therefore, exogenously applied nano-silicon could be used to improve the CWP and seed and biological yields of faba bean plants under conditions with low water availability in arid environments.